Laporan Kasus Perempuan 70 Tahun dengan Chronic Kidney Disease Stage V Non Dialisis di RSU Cut Meutia Lhokseumawe - Hasanatul Khairiyah; Yenni Sulisma (Pusat Riset dan Inovasi Nasional, 2025)
Chronic kidney disease (CKD) is defined as kidney damage or estimated glomerular filtration rate (eGFR) less than 60 ml/min/1.73 mt2, which lasts for 3 months or more, regardless of the cause. CKD initially shows no signs and symptoms but can progress to kidney failure. Screening, diagnosis, and appropriate management by primary care physicians. The purpose of this study was to describe the symptoms and management of CKD in elderly patients who did not undergo hemodialysis. The method in this study was a case report. Primary data were obtained through anamnesis and physical examination. The results obtained were a 70-year-old woman was brought to the Emergency Room of Cut Meutia Hospital with complaints of shortness of breath since 1 day SMRS. In the Emergency Room, the patient complained of weakness and looked pale. The patient also complained of nausea but did not vomit and the amount of urine was small. Physical examination found anemic conjunctiva and CVA percussion pain. Laboratory examination showed the patient's hemoglobin level was 4.81 g/dL. The management given was only pharmacological because the patient refused hemodialysis. The prognosis of this case study is dubia ad malam.